Efficacy and Safety of Xueshuantong Injection on Acute Cerebral Infarction: Clinical Evidence and GRADE Assessment - Lyu, Jian; Xie, Yanming; Sun, Menghua; Zhang, Lidan (Frontiers in Pharmacology, 2020)
Introduction: Xueshuantong injection (XST), a Chinese Medicine, is clinically effective in treating acute cerebral infarction (ACI). However, the meta-analysis of XST combined with conventional treatments (CTs) on ACI remain unexplored. This study was to investigate the efficacy and safety of XST combined with CTs on patients with ACI. Methods: Randomized controlled trials (RCTs) were screened from PubMed, EMBASE, Web of Science, Cochrane Library and four Chinese's database. The meta-analysis was performed using RevMan 5.3 and STATA 16.0. The GRADE assessment was performed by the GRADEprofiler (GRADEpro version: 3.6). Pooled relative risk (RR) estimates and 95% confidence intervals (CIs) were calculated. Results: Forty studies were included, involving a total of 3,868 patients. XST combined with CTs performed significantly better than CTs alone on the overall response rate (ORR) after treated (RR = 1.21, 95% CI = 1.17−1.25, P < 0.001). There were no significant differences in the incidence of adverse reactions between the experimental group (XST plus CTs) and control group (CTs alone ). Groups treated with XST substantially decreased the National Institutes of Health Stroke Scale (NIHSS) score compared to the groups without XST (WMD = −5.31, 95% CI = −6.40 to −4.22, P < 0.001). Activities of daily living (ADL) score were meaningfully better in the experimental group (XST plus CTs) than in the control group (CTs alone ) (WMD = 12.51, 95% CI = 5.6−19.38, P < 0.001). XST combined with CTs showed significantly higher improvements in high-sensitivity C-reactive protein (hs-CRP) (WMD = −2.47, 95% CI = −3.11 to −1.82, P < 0.001), interleukin 6 (IL-6) (WMD = −13.66, 95% CI = −17.80 to −9.51, P < 0.001) than CTs alone. The GRADE assessment indicates that the comprehensive quality of this evidence is low. Conclusions: This meta-analysis and GRADE assessment conditionally recommend that XST combined CTs can increase the overall response rate, ameliorate neurological deficit, improve activities of daily living function more than CTs alone. A significant reduction in the hs-CRP and IL-6 level was observed when XST was combined with CTs.